If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(7x + -2) + 5(19 + -3x) = 3(4x + 3) + -6 Reorder the terms: 4(-2 + 7x) + 5(19 + -3x) = 3(4x + 3) + -6 (-2 * 4 + 7x * 4) + 5(19 + -3x) = 3(4x + 3) + -6 (-8 + 28x) + 5(19 + -3x) = 3(4x + 3) + -6 -8 + 28x + (19 * 5 + -3x * 5) = 3(4x + 3) + -6 -8 + 28x + (95 + -15x) = 3(4x + 3) + -6 Reorder the terms: -8 + 95 + 28x + -15x = 3(4x + 3) + -6 Combine like terms: -8 + 95 = 87 87 + 28x + -15x = 3(4x + 3) + -6 Combine like terms: 28x + -15x = 13x 87 + 13x = 3(4x + 3) + -6 Reorder the terms: 87 + 13x = 3(3 + 4x) + -6 87 + 13x = (3 * 3 + 4x * 3) + -6 87 + 13x = (9 + 12x) + -6 Reorder the terms: 87 + 13x = 9 + -6 + 12x Combine like terms: 9 + -6 = 3 87 + 13x = 3 + 12x Solving 87 + 13x = 3 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 87 + 13x + -12x = 3 + 12x + -12x Combine like terms: 13x + -12x = 1x 87 + 1x = 3 + 12x + -12x Combine like terms: 12x + -12x = 0 87 + 1x = 3 + 0 87 + 1x = 3 Add '-87' to each side of the equation. 87 + -87 + 1x = 3 + -87 Combine like terms: 87 + -87 = 0 0 + 1x = 3 + -87 1x = 3 + -87 Combine like terms: 3 + -87 = -84 1x = -84 Divide each side by '1'. x = -84 Simplifying x = -84
| 2y+110+35=180 | | 5a+7=3a-15 | | 18x+4=58 | | (6x+7)-(4+5x)=12 | | (4*2k)+3k-2= | | 9+10r-2=9r+35-3r | | 48x^2+24x+3=0 | | x=-60+2s | | 2y+110+35=360 | | 3(x-1)-24=2(-1-x) | | 2w^2-3w-27=0 | | 4x+18=58 | | 2x+40=110 | | 10x+6=64 | | 3[3f+1]=7[2f+9] | | 3(5-4t)-t=18 | | 2[3e-7]=5[6-e] | | 3[2d-9]+5d=105 | | 40x+60(x-2)=380 | | 8c-4[c+3]=8 | | 41-32=r | | 7[5b+6]=-63 | | 6[a-3]=24 | | 8.5a+6(20-a)=20(7) | | .5(60+x)=s | | 2x+6=4x+5+1 | | 8.5+6(20-x)=20(7) | | 4a+b=4 | | 0.75x+0.15(90-x)=90(0.35) | | 6x-10=64 | | 2p-4=44+8p | | Y=-x^2+20x-64 |